Between Needs and Taboos: Sexuality and Reproductive Health Education for High School Students - Diana Teresa Pakasi; Reni Kartikawati (Makara Journal of Health Research, 2013)
This paper examines reproductive health and sexuality education for adolescents that has been conducted by government and non-government at the high school level. This paper is based on a research using mixed methods of quantitative methods that are supported by qualitative. Quantitative methods are surveys conducted to 918 students and 128 high school teachers and supported by focus group discussions and in-depth interviews in eight cities in Indonesia. Focus group discussions conducted to civil society organizations, teacher forums, and youth groups, while in-depth interviews conducted to local government, parents, school committees, and religious/community leaders. The results show that the reproductive and sexual health education does not match the reality of sexual behavior and sexual risk faced by teenagers because: (1) reproductive health and sexuality education that is given to the high school level is more focused on the biological aspects alone, (2) There is still a notion that sexuality is a taboo to be given at school, (3) the sexuality education tends to emphasize the dangers of premarital sex from the moral and religious point of view, (4) the sexuality education has not looked at the importance of aspects of gender relations and rights of adolescents in adolescent reproductive and sexual health. The construction of adolescent sexuality and the discourse on sexuality education contribute to the content and methods of sexual